KETEPATAN KODE PENYAKIT PADA DOKUMEN REKAM MEDIS DI PUSKESMAS PLUMBON - Eva Rahmawati; Tuti Herawati; Fardhoni (Jurnal Kesehatan Mahardika, 2021)
The implementation of coding done in the medical record should be done very thoroughly, precisely and accurately according to the diagnostic code that exists in ICD-10. If there is an error in coding, it will have a bad impact on the patient, puskesmas or hospital. But in the fact found in the field there are still problems in the implementation of the accuracy of the encoding of disease diagnosis based on ICD-10. The purpose of this research is to describe the accuracy of disease code in the medical record in Puskesmas Plumbon. The population in this study was the entire quarterly medical record document of year 2020 with a total of 1,098 medical record documents with a total sample of 92 documents using simple random sampling technique. This study was conducted in Plumbon Puskesmas Medical record unit on 20 June 2020. The method used is descriptive with a quantitative approach. The data collection procedures used are by observation and checklist sheet. The population in this study was the entire quarterly medical record document of year 2020 with a total of 1,098 medical record documents with a total sample of 92 documents using simple random sampling technique. This study was conducted in Plumbon Puskesmas Medical record unit on 20 June 2020. The results of the study obtained from 92 samples of medical record documents, the appropriate disease code in accordance with the ICD-10 as much as 39 (42.39%) and improper code of 53 (57.61%). There is still an imprecision of unsuitable disease code due to coding officers that do not include the 4th character. It is best to need a fixed procedure in accordance with WHO provisions for coding the disease to make the koder more thorough in determining the disease code.